The Philosophical and Ethical Analysis Of The Soul and Purity In The Teachings Of Fazl Ibn Ahmad - Saipova Mavjuda Karimjanovna (Buletin Antropologi Indonesia, 2025)
This article provides information on the philosophical analysis of the soul and purity according to Fazl ibn Ahmad. The relationship between the soul and purity is discussed in his work “Iddatul Uqul” and “Umdatul Ma’qul” (The Promises of the Intellect and the Foundations of What the Intellect Considers Appropriate). In the process of building New Uzbekistan, the teachings of Rumi, especially the ideas of Fazl ibn Ahmad, remain significant in educating young people to become spiritually sound individuals and in elevating them morally in today’s complex era. Today, the effective use of Fazl ibn Ahmad’s “Iddatul Uqul” and “Umdatul Ma’qul” (The Promises of the Intellect and the Foundations of What the Intellect Considers Appropriate) in social development, societal welfare, and the fulfillment of human needs is emphasized.